The Design and Use of Questionnaires in Educational Research: A New (Student) Researcher Guide - Holmes, Andrew G D (Innovare Journal of Education, 2023)
Final-year undergraduate and master’s students often collect data for a research project through a questionnaire. However, novice researchers may have little or no experience designing and using questionnaires and struggle with both designing and operationalizing one. This paper explores and explains, from a theoretical and practical perspective, how a novice researcher may go about the process. Its intended target audience is final-year undergraduate and postgraduate students undertaking a research project, such as a dissertation. Its purpose is to provide the necessary fundamental knowledge for learners to develop their research questionnaires for qualitative data collection.